2020
DOI: 10.18178/ijiet.2020.10.12.1480
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Development and Application of Virtual Reality (VR) Training Platform for Testing, Inspection and Certification Industry

Abstract: The Virtual Reality (VR) training is one of modern simulation tools which has been used to help train up staffs to operate equipment and facilities, as well as handling emergency situations in different industries. This paper discusses the theories supporting the adoption of VR technologies in the laboratories and pros/cons of Virtual Reality Training systems. Virtual reality technologies have been applied to different types of trainings in many industries, such as product design and manufacturing, facilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the following, the further steps of the planning are presented. For sub-step 1.2 Derivation of requirements, the selection of bibliographic sources is made on the databases Scopus and web of science, because for related SLR in the area of Lean Management (Salentijn et al 2021), Virtual Reality (Domingueti et al 2021;Mak et al 2020), Augmented Reality (Ho et al 2022;Quandt and Freitag 2021: 4 f), Education (Checa and Bustillo 2020) and Concepts these databases have provided the most results and thus the largest possible overview can be achieved. With the catchwords, the three topic areas VR/AR (assistance systems), Lean Management and Six Sigma as well as education are to be subdivided.…”
Section: Rq3mentioning
confidence: 99%
“…In the following, the further steps of the planning are presented. For sub-step 1.2 Derivation of requirements, the selection of bibliographic sources is made on the databases Scopus and web of science, because for related SLR in the area of Lean Management (Salentijn et al 2021), Virtual Reality (Domingueti et al 2021;Mak et al 2020), Augmented Reality (Ho et al 2022;Quandt and Freitag 2021: 4 f), Education (Checa and Bustillo 2020) and Concepts these databases have provided the most results and thus the largest possible overview can be achieved. With the catchwords, the three topic areas VR/AR (assistance systems), Lean Management and Six Sigma as well as education are to be subdivided.…”
Section: Rq3mentioning
confidence: 99%
“…An extensive body of research on the application of VR in an industrial context [2,4,5] demonstrates the potential to enhance and shift existing practices. Indeed, the flexibility of simulations and interactions in VR offers a range of benefits to the training and learning of maintenance technicians [6][7][8], providing them with safe and novel ways of practicing.…”
Section: Related Workmentioning
confidence: 99%
“…The major application is split into two areas: (1) pre-job training and (2) on-site support [2]. VR-based pre-job training is a well-studied matter, which demonstrates positive effects on the performance and accuracy of maintenance technicians coupled with a decreased error rate and training time [6][7][8]20,29]. A study by Winther et al [11], for instance, demonstrated that after 20 min of training in VR, participants were able to perform maintenance operations over a realworld dosing pump.…”
Section: Industrial Training In Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…Актуальне застосування дана технологія знаходить у контролюванні процесу будівництва. Інженер з будівельного контролю, за наявності VR-окулярів, що мають вбудований GPSприймач, у режимі реального часу обходить будівельний майданчик та аналізує накладені системою проектні дані на реальне зображення встановленої конструкції або частини інженерної мережі [14].…”
unclassified